Human factor and working conditions in the hotel sector, Leoncio Prado province, Huanuco - Bazan-Rivera, Jimmy R. (2022)
The human factor is the fundamental resource to achieve the success of a company, however, few investigations indicate its influence on working conditions. The objective of the study was to analyze the human factor and decent work conditions in 110 housekeeping and reception workers, distributed in 34 lodging establishments in the province of Leoncio Prado. The research is explanatory, transversal and was based on the concept of decent work proposed by the international labor organization. For data collection, a survey was applied, using a questionnaire of 15 questions, with a content validity of equal to 0.997 and a reliability of Cronbach's alpha equal to 0.80. In the results it was found that 51.95% of the workers are in regular basic education, 57.5% work for up to one year and 62% have not received any type of training. Through the multinominal probit model, it is concluded that the human factor indicators: years of studies, experience and job training increase the probability of having decent working conditions by 9.34%, 11.1% and 86.7% respectively.